The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1016/0925-8388(94)90213-5
|View full text |Cite
|
Sign up to set email alerts
|

Complex antiferromagnetic order of CeCuSn

Abstract: CeCuSn, which forms in the hexagonal CaIn2-type of structure, orders antiferromagnetically at 8.6 K. A second maximum at about 7.35 K seen in the temperature dependence of the specific heat indicates a rearrangement of the antiferromagnetic structure. The antiferromagnetic ordering is also reflected in the temperature dependence of the electrical resistivity. Upon application of magnetic fields up to 5 T, a complex development of magnetic phases can be followed by monitoring the temperature dependencies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
5
12
0
Order By: Relevance
“…The top panel shows the zero field cooled (ZFC) and field cooled (FC) χ(T ) curves for α-CeCuSn measured in a field of 100 Oe. Earlier heat capacity studies of annealed CeCuSn have shown two magnetic transitions at 8.6 and 7.4 K [12]. Consistent with these temperatures, there is a sudden rise in χ(T ) of α-CeCuSn around 8.6 K as if it were a ferromagnetic ordering (vide infra).…”
Section: Physical Property Measurementssupporting
confidence: 55%
See 1 more Smart Citation
“…The top panel shows the zero field cooled (ZFC) and field cooled (FC) χ(T ) curves for α-CeCuSn measured in a field of 100 Oe. Earlier heat capacity studies of annealed CeCuSn have shown two magnetic transitions at 8.6 and 7.4 K [12]. Consistent with these temperatures, there is a sudden rise in χ(T ) of α-CeCuSn around 8.6 K as if it were a ferromagnetic ordering (vide infra).…”
Section: Physical Property Measurementssupporting
confidence: 55%
“…Contrary to α-CeCuSn, there is only one steplike anomaly around 7.9(1) K which we consider as T N for β -CeCuSn. It may be recalled that the magnetic phase diagram of CeCuSn given by Nakotte et al indicates that magnetic anisotropy is intrinsic to the CeCuSn compound [12].…”
Section: Physical Property Measurementsmentioning
confidence: 99%
“…They found that former compound shows AFM ordering with TN= 8 K with a weak spontaneous magnetization while the later compound shows AFM ordering with TN=10 K with no spontaneous magnetization. Nakotte et al [266] reported three magnetic transitions in CeCuSn. They reported that two magnetic transitions, AF1 and AF2, are seen in zero field, while the third magnetic phase transition, AF3 is only stable in an applied field.…”
Section: Rcux Compoundsmentioning
confidence: 99%
“…CeCuSn was reported to order antiferromagnetically below T N Ϸ 8.6 K. [3][4][5] . In addition, a broad double-peak feature in the zero-field specific heat was taken to indicate a second magnetic transition at about 7.5 K. 3 Subsequent muon spin relaxation ͑SR͒ experiments indicated an unusual evolution of the magnetic ordering in CeCuSn, starting with the onset of short-range correlations at 11 K leading to spin freezing around 8.6 K, and finally a coexistence of long-range ordered and spin-frozen phases below 7.5 K. 6 Recently, we synthesized single crystals of CeCuSn, allowing us to investigate the magnetic structure in greater detail.…”
mentioning
confidence: 99%
“…The crystal structure of CeCuSn has been reported to be of the hexagonal CaIn 2 type ͑space group P6 3 / mmc͒. 3,5 Singlecrystal x-ray diffraction showed that our CeCuSn samples form in the hexagonal GaGeLi-type crystal structure with lattice parameters a = 4.59 Å and c = 7.90 Å. However, it has also been suggested that CeCuSn may form in an ordered variant, the GaGeLi-type structure ͑space group P6 3 mc͒, which is shown schematically in Fig.…”
mentioning
confidence: 99%